Cessation of the pacifier sucking habit and self-correction of the anterior open bite in the primary dentition: case report - Gabriela Petri de BORTOLO; Lilian Citty SARMENTO; Ana Paula Martins GOMES; Ana Maria Martins GOMES; Maria Christina Thomé PACHECO; Elâine Cristina Vargas DADALTO (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Objective: To evaluate the effectiveness of play strategies to break the pacifier-sucking habit and induce self-correction of the anterior open bite in the primary dentition. Methods: Data collection took place at the Pediatric Dentistry clinic of a public education institution. Three children, aged between 3 and 4 years old, using a pacifier and presenting with a 2 to 5 mm anterior open bite, participated in the research. Pediatric dental guidance was imparted to educate the family and to provide play strategies for the child by means of an illustrated book about the pacifier fairy. Results: After the first consultation, two children quit their pacifier habit. Subsequent consultations were devoted to positive reinforcement and follow-up of the self-correction of the anterior open bite. The third child required four visits to stop the pacifier habit, but other habits persisted and the open bite was only corrected after intervention by a multidisciplinary team. Conclusions: After receiving orientation from the professionals, the parents/guardians cooperated in stimulating the child, and the play activities were effective in encouraging the child to stop sucking on the pacifier, permitting self-correction of the anterior open bite. Bottle feeding, tongue interposition and mouth breathing may hinder the spontaneous correction of the anterior open bite after the pacifier habit is abandoned, requiring multidisciplinary intervention.